SOSIALISASI IMPLEMENTASI APLIKASI PETANI DAN NELAYAN PINTAR: SOCIALIZATION OF THE IMPLEMENTATION OF SMART FARMERS AND FISHERMEN APPLICATIONS - Nofri Yudi Arifin (Universitas Muhammadiyah Manado, 2022)
The implementation of learning at this time needs to be supported by technology-based learning media. Technology-based media can make people adapt to the current developments in technology. One of the technology-based information media that can be used as a support for existing media is in the application. There are various types of applications such as smart farmer and fisherman applications. In this community service the author will introduce one technology-based application, namely the application of smart farmers and fishermen. The purpose of this activity is that participants are expected to help facilitate access for farmers and fishermen to obtain or exchange information.